2014
DOI: 10.1016/j.celrep.2014.08.040
|View full text |Cite
|
Sign up to set email alerts
|

RET Recognition of GDNF-GFRα1 Ligand by a Composite Binding Site Promotes Membrane-Proximal Self-Association

Abstract: The RET receptor tyrosine kinase is essential to vertebrate development and implicated in multiple human diseases. RET binds a cell surface bipartite ligand comprising a GDNF family ligand and a GFRα coreceptor, resulting in RET transmembrane signaling. We present a hybrid structural model, derived from electron microscopy (EM) and low-angle X-ray scattering (SAXS) data, of the RET extracellular domain (RET(ECD)), GDNF, and GFRα1 ternary complex, defining the basis for ligand recognition. RET(ECD) envelopes th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
71
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(83 citation statements)
references
References 34 publications
(37 reference statements)
10
71
0
Order By: Relevance
“…To stimulate RET tyrosine kinase activity from the extracellular environment, these GFLs first need to assemble into a complex with their glycosylphosphatidylinositol (GPI)-anchored co-receptors, the GDNF receptor-α family (GFRα1-4), after which the GFL-GFRα complex recruits RET to form cognate and non-cognate heterodimers. The RET-GFL-GFRα complex (the RET 'ternary' complex) has a 2:2:2 stoichiometry, meaning a dimer of GDNF binds two co-receptor molecules that at the same time recruit two RET receptor molecules and exhibits positive cooperativity (Schlee et al 2006, Goodman et al 2014. Recently, the architecture of RET extracellular domain (ECD) was revealed by small angle X-ray scattering (SAXS) and electron microscopy (EM).…”
Section: Introductionmentioning
confidence: 99%
“…To stimulate RET tyrosine kinase activity from the extracellular environment, these GFLs first need to assemble into a complex with their glycosylphosphatidylinositol (GPI)-anchored co-receptors, the GDNF receptor-α family (GFRα1-4), after which the GFL-GFRα complex recruits RET to form cognate and non-cognate heterodimers. The RET-GFL-GFRα complex (the RET 'ternary' complex) has a 2:2:2 stoichiometry, meaning a dimer of GDNF binds two co-receptor molecules that at the same time recruit two RET receptor molecules and exhibits positive cooperativity (Schlee et al 2006, Goodman et al 2014. Recently, the architecture of RET extracellular domain (ECD) was revealed by small angle X-ray scattering (SAXS) and electron microscopy (EM).…”
Section: Introductionmentioning
confidence: 99%
“…Although it was originally thought that CLD1-3 of RET was involved in direct binding from results obtained through mutagenesis studies, a direct interaction between CLD1-3 and the GDNF-GFR␣1 complex has not been observed (53,54). Instead, it has been proposed that CLD1-3 contributes to the stability of the tertiary structure of the GDNF-GFR␣1-RET complex by forming a secondary dimerization site to trap the GDNF-GFR␣1 binary complex (14). These studies predict that RET ⌬E3 , which forms a fused CLD1-CLD2 region, likely gives rise to a less stable tertiary GDNF-GFR␣1-RET complex compared with full-length RET.…”
Section: ⌬E3mentioning
confidence: 95%
“…Molecular Modeling-This analysis was performed as described previously (14). Models of cadherin-like domains 1-4 were taken from PDB code 4UX8, defined by a combination of EM and small angle x-ray scattering analyses.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations